Endocervical metastasis of pancreatic cancer: A rare case report of long-term survival - Yuichi Kinoshita; Katsuhiko Yoshizawa; Takashi Yuri; Airo Tsubur; Nobuaki Shikata (Elsevier, 2016)
Most uterine cervix adenocarcinomas are primary tumors. Here, we report a case of pancreatic cancer that metastasized to the uterine cervix. The patient was a 77-year-old Jehovah's Witness whose pancreatic cancer had been diagnosed 10 years previously. As she had refused blood transfusion on religious grounds, the tumor only underwent segmental excision, followed by radiofrequency wave therapy and chemotherapy. During a routine health examination 6 years after her pancreatic tumor resection, a tumor in the left lower lobe of her lung was found, and then removed. Three years after the lung surgery, her serum CA19-9 increased. A detailed examination found tumors in the ascending colon and uterine cervix. She underwent chemotherapy and radiotherapy after a right hemicolectomy, endocervical biopsy, and endocervical cytology. At present, about 10 years after her initial diagnosis, she is alive with no recurrence or metastatic findings. Morphologically, well-differentiated pancreatic adenocarcinoma is similar to endocervical type adenocarcinoma and adenocarcinoma in situ of the uterine cervix. Therefore, careful immunohistochemical examination and clear understanding of the patient's clinical information are needed in diagnosing adenocarcinoma in the uterine cervix.